2017
DOI: 10.1007/s12541-017-0197-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of heat treatment on microstructures and tensile properties of IN718/TiC nanocomposite fabricated by selective laser melting

Abstract: Effects of heat treatment on microstructures and tensile properties of IN718/TiC nanocomposite fabricated by selective laser melting

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Parts showed a remarkable improvement in mechanical properties (ultimate tensile strength: (633 ± 34) MPa vs. (1,207 ± 4) MPa, elongation at break: (1.3 ± 0.3) % vs. (5.7 ± 0.2) %) as compared to specimen produced from the non-functionalized feedstock. Yao et al (2017), reported the manufacture of near fully dense TiC matrix-reinforced Inconel 718 parts characterized by a refined microstructure from a composite powder produced by dry coating of gas atomized IN718 with TiC nanoparticles using a tumbling mixer. Specimens built from the composite powder showed an improved tensile strength due the grain refinement.…”
Section: Nickel Alloy Feedstock Powdersmentioning
confidence: 99%
“…Parts showed a remarkable improvement in mechanical properties (ultimate tensile strength: (633 ± 34) MPa vs. (1,207 ± 4) MPa, elongation at break: (1.3 ± 0.3) % vs. (5.7 ± 0.2) %) as compared to specimen produced from the non-functionalized feedstock. Yao et al (2017), reported the manufacture of near fully dense TiC matrix-reinforced Inconel 718 parts characterized by a refined microstructure from a composite powder produced by dry coating of gas atomized IN718 with TiC nanoparticles using a tumbling mixer. Specimens built from the composite powder showed an improved tensile strength due the grain refinement.…”
Section: Nickel Alloy Feedstock Powdersmentioning
confidence: 99%
“…One of the most widespread metal AM process is selective laser melting (SLM) or direct metal laser sintering (DMLS) [7,8]. In this process, a high-density object is built up layer by layer through the consolidation of metal powder particles with a focused laser beam that selectively scans the surface of the powder bed [3,[9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, researchers have used SLM technology to manufacture various MMNCs and biocomposites [4] [14]. For instance, the typically investigated nickelbased nanocomposites include TiC/Inconel 718 nanocomposites [15][16], carbon nanotube/Inconel 625 composites [17] and TiN/Inconel 718C composites [18]. The findings from these studies demonstrated that, compared to the as-fabricated matrix materials, SLM-fabricated nanocomposites exhibited higher tensile strength but lower elongation due to the ensuing grain refinement.…”
Section: Introductionmentioning
confidence: 99%